Education and Skills for Inclusive Growth, Green Jobs and the Greening of Economies in Asia: Case Study Summaries of India, Indonesia, Sri Lanka and Viet Nam - Brajesh Panth (Technical and Vocational Education and Training: Issues, Concerns and Prospects, 2018)
This book presents an overview of the main research findings and case studies concerning education and skills for inclusive growth, green jobs and the greening of economies. Focusing on India, Indonesia, Sri Lanka and Viet Nam, it discusses government and business sector responses to these issues and how Technical and Vocational Education and Training (TVET) systems and institutions are addressing both the renewal of curricula in the context of green growth dynamics, and patterns of training and skills development to meet demands. In addition, the book examines cross-country issues, concerns and prospects regarding education and skills for inclusive growth and green jobs for the four countries. These include critical themes and issues in the selected industry sectors triggering a demand for green jobs in the region; how industry is responding to those demands; areas impeding the transition from traditional to green practices; the importance of skills development; the role of TVET in addressing industry needs; and reasons for the slow response of TVET to green skills.While other studies conducted in Asia - and internationally - on the same topic have largely relied on secondary sources, this study conducted by the Asian Development Bank and the Education University of Hong Kong (ADB-EdUHK) is unique in that the findings, conclusions and recommendations reported on are based on primary data. As part of the study, TVET providers, business enterprises, policy makers and practitioners were surveyed using questionnaires and face-to-face interviews. In addition, workshops were held in each of the four countries to ascertain the views of key stakeholders in government, nongovernment organisations, members of the international development community, TVET providers and members of the business sector.The book also provides summaries of the case studies undertaken for India, Indonesia, Sri Lanka and Viet Nam.